L'Arrière-pays de Yves Bonnefoy, viagem e escrita de si - Amorim, Pablo Simpson Kilzer [UNESP] (My University, 2014)
This essay attempts to approach the book L’Arrière-pays by Yves Bonnefoy from two central ideas: the notion of travel and autobiographical writing. They belong to the poet’s project, according to which, since L’Improbable published in 1959, and with reference to Baudelaire, “poetry and travel are of the same substance”. Invited by Albert Skira to participate in the collection  Sentiers de la création, Yves Bonnefoy produces in  L’Arrière-pays  a long essay in which he combines art criticism, philosophical reflection and personal narrative. With narrative projects abandoned or transformed into poems, as in the case of L’Ordalie, incorporated into the book Du Mouvement et de l’immobilité de Douve (1953), Yves Bonnefoy in L’Arrière-pays establishes a first path to reconsider the association between narrative and fiction and, for that reason, is the central text of what the poet called his «conversion».

Este ensaio pretende abordar o livro L’Arrière-pays de Yves Bonnefoy a partir de duas reflexões centrais: as noções de viagem e de escrita autobiográfica. Elas são constitutivas do projeto do poeta, para quem desde L’Improbable, publicado em 1959, e em referência a Baudelaire, “poesia e viagem são de uma mesma substância”. Convidado por Albert Skira para figurar na coleção Sentiers de la création, Yves Bonnefoy produz em L’Arrière-pays um longo ensaio em que conjuga crítica de arte, reflexão filosófica e relato pessoal. Com seus projetos narrativos abandonados ou transformados até então em poemas, como é o caso de L’Ordalie, incorporado ao livro Du mouvement et de l’immobilité de Douve (1953), Yves Bonnefoy em L’Arrière-pays estabelece um primeiro caminho para a reconsideração da associação entre narrativa e ficção e, por isso, é o texto central daquilo que o poeta denominou de sua “conversão”
Yves Bonnefoy’s L’arrière-pays, travel and self-writing
Keywords: Yves Bonnefoy; Literatura Francesa; Poesia; Autobiografia; Viagem; French Literature; Poetry; Autobiography; Travel